Diagnosis and treatment of vestibular disorders - Babu, Seilesh; Schutt, Christopher A.; Bojrab, Dennis I. (Cham, Switzerland : Springer, 2019)
This text reviews the current understanding of vestibular anatomy allowing for a framework of reference, and how it's applied to vestibular testing, diagnosis and management of dizziness. Vestibular testing is an important tool in the evaluation and management of the patient with dizziness. It aids in establishing a diagnosis and determining the side or site of the lesion. In addition, it guides practitioners in selection of treatment and allows the ability of the patient's condition to be evaluated over its time course. Common vestibular pathologies such as benign positional vertigo, Meniere's disease, multisensory imbalance, vestibular neuritis, superior canal dehiscence, and vestibular migraine will be addressed in a concise and understandable manner. The text follows a clear format in which the etiology, pathophysiology, diagnostic features and medical or surgical management of such pathologies are discussed. The book gains increased importance as superior canal dehiscence and vestibular migraine are relatively new hot topics. Lastly, relatively rare entities such as bilateral vestibular hypofunction, pediatric vestibular disorders and central vestibular disorders are discussed. This text serves as a complete reference for clinicians, students and researchers interested in this common and severe disorder allowing for improved patient care and advancement of knowledge in the field. Chapters are written by acknowledged experts, allowing summary review of the newest and most up-to-date understanding of scientific information. Diagnosis and Treatment of Vestibular Disorders will be an invaluable resource for otolaryngologists, neurologists, otologists and neurotologists, basic science and translational researchers with interests in the vestibular system, fellows and residents in aforementioned fields, and general practitioners with an interest in patients with symptoms of dizziness.
Sinusoidal Harmonic Acceleration InterpretationNormal Sinusoidal Harmonic Acceleration Response; Unilateral Peripheral Impairments; Bilateral Peripheral Impairments; Central Impairments; Sinusoidal Harmonic Acceleration Clinical Summary; Velocity Step Testing; Velocity Step Stimuli; Physiologic Vestibular Ocular Reflex Response; Low-Velocity Step Testing; High-Velocity Step Testing; Clinical Response Patterns for Velocity Step Testing; Low-Velocity Step Response Interpretation; High-Velocity Step Response Interpretation; Chapter Summary; References; Chapter 7: Dynamic Posturography
Includes index.
Online resource; title from PDF title page (SpringerLink, viewed February 4, 2019).
Added to collection customer.56279.3
Keywords: Vestibular apparatus -- Diseases -- Diagnosis; Vestibular apparatus -- Diseases -- Treatment; Vestibular apparatus -- Diseases -- Treatment; Electronic books